2019
DOI: 10.21802/gmj.2019.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Color Vision Deficiency in Medical Students in Jammu & Kashmir, India

Abstract: Non recognition of any of the three colors is known as color blindness. Color blindness is the commonly used term for deficiency of color vision. Word color blindness is a misnomer as anyone labeled as it, is extremely rare to be totally color blind hence more correctly called color vision deficiencies (CVD). Color vision is a function of three types of cone pigments present in retina. The incidence of Color vision deficiency is common in medical profession and affects the diagnosis and treatment of patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…There are prevalence variations in red-green color blindness by population, race, tribe and ethnic (Karolina et al, 2019). The data showed that the number of male color-blind people is more than female color blind so that it can prove that color blindness is a disorder caused by the recessive gene c is linkage on X-chromosome (Nazeer et al, 2019). Males only have one X chromosome so that the color-blind gene will be easily expressed (Moudgil et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are prevalence variations in red-green color blindness by population, race, tribe and ethnic (Karolina et al, 2019). The data showed that the number of male color-blind people is more than female color blind so that it can prove that color blindness is a disorder caused by the recessive gene c is linkage on X-chromosome (Nazeer et al, 2019). Males only have one X chromosome so that the color-blind gene will be easily expressed (Moudgil et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The men allele frequency of color blind was higher than female. Because color blindness is more common in men (Nazeer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In common with the findings of the present study, previous studies reported a higher prevalence of color blindness among males. The prevalence of color blindness among males can be attributed to a gene defect in the X chromosome in the Xq28 band ( 13 , 14 ). The relatively low prevalence of color blindness among the males in our study may be due to the low number of males in our study population relative to that of females.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In addition to refractive errors, significant number of medical students were found to have color vision deficiency too. [10][11][12] The prevalence of eye defects among medical students seems to be at alarming rate but very few studies have been done to study the gravity of ocular problems as well as assess the factors contributing to visual impairment among medical students in Nepal. This study aimed to provide basic data regarding the ocular problems among the medical students which may aid in pre-assessment of visual function before enrollment in medical school enabling the detection and treatment of any ocular problems that may interfere with academic pursuits.…”
Section: Introductionmentioning
confidence: 99%